ANALISIS TINGKAT KESEHATAN BANK DENGAN PENERAPAN METODE RGEC (RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNINGS DAN CAPITAL) PADA PT.BANK BENGKULU - Yun Fitriano; Ririn Marlina Sofyan (Unib Press Universitas Bengkulu, 2019)
This study aims to determine the health level of PT. Bank Bengkulu in the 2014-2016 period if measured using the RGEC method (Risk Profile, Good Corporate Governance, Earnings, and Capital). Based on the results of the assessment of bank soundness by applying the RGEC method at PT. Bank Bengkulu is seen from factors, namely 1. Risk Profile, the results of the 2014 NPL ratio of 0.39%, in 2015 amounted to 0.39%, and in 2016 amounting to 0.33% can be said to be very healthy. The results of the LDR ratio in 2014 amounted to 85.79%, in 2015 amounted to 91.05%, and in 2016 amounting to 93.31% this could be said to be quite healthy. 2. Good Corporate Governance in the 2014-2016 period of 89.33% can be said to be very healthy. 3. Eanings, the results of the 2014 ROA ratio amounted to 3.69%, in 2015 amounted to 3.29%, and in 2016 amounting to 3.02% this could be said to be very healthy. The results of the BOPO ratio in 2014 amounted to 74.10%, in 2015 amounted to 80.54%, and in 2016 amounting to 77.71% this could be said to be very healthy. 4. Capital, the results of the 2014 CAR ratio amounted to 16.99%, in 2015 amounted to 21.39%, and in 2016 amounting to 19.07% can be said to be very healthy. The results of the health research at PT. Bank Bengkulu in the 2014-2016 period showed that PT. The Bengkulu Bank gets PK 1, which is very healthy.